The Scholar Relation Analysis Map Using Linked Open Data on the Research Platform of the Research Information Sharing Service (RISS) - Jang, Sang-hyun (International Journal of Knowledge Content Development & Technology, 2022)
The outbreak of the COVID-19 pandemic facilitated opportunities for contact-free (or “contactless”) academic activities. In particular, academic activity has become active on online platforms, and researchers have demonstrated a growing tendency to search information more accurately and conveniently on the platforms that carry numerous academic information. In 1998, the Korea Education and Research Information Service (KERIS), a research institute funded by the Ministry of Education, developed a platform that shares and collects academic research information, namely, the Research Information Sharing Service (RISS). The RISS platform encompasses all domestically-produced research information and the overseas research information. The RISS consists of union catalogues service, inter-library loan service, dCollection system, research information analytics service, and overseas theses information service. The RISS has accumulated not only the domestic theses and dissertations but also various academic data over the past two decades. There has also been an increasing demand for easily obtaining the platform data added in real time. As such, using the liked open data (LOD) through the RISS, the KERIS has linked data with others and formed a useful environment for using data to help the researchers with conducting their academic activities. By analyzing and processing the data produced on the RISS platform and reflecting the users’ patterns of uses, the KERIS has implemented a new scholar relation analysis map (“SAM”) service. In this context, this article introduces thesis-researcher relation analysis service, thesis usage analysis service, thesis-researcher impact analysis service, and latest research trend analysis service.